Classification of paroxysmal events and the four‐dimensional epilepsy classification system. Issue 1 (27th March 2019) - Lüders, Hans; Vaca, Guadalupe Fernandez‐Baca; Akamatsu, Naoki; Amina, Shahram; Arzimanoglou, Alexis; Baumgartner, Christoph; Benbadis, Selim R.; Bleasel, Andrew; Bermeo‐Ovalle, Adriana; Bozorgi, Alireza; Carreño, Mar; Devereaux, Michael; et al.
ABSTRACT: This educational review describes the classification of paroxysmal events and a four‐dimensional epilepsy classification system. Paroxysmal events are classified as epileptic and non‐epileptic paroxysmal events. Non‐epileptic events are, in turn, classified as psychogenic and organic paroxysmal events. The following four dimensions are used to classify epileptic paroxysmal events: ictal semiology, the epileptogenic zone, etiology, and comorbidities. Efforts are made to keep these four dimensions as independent as possible. The review also includes 12 educational vignettes and three more detailed case reports classified using the 2017 classification of the ILAE and the four‐dimensional epilepsy classification. In addition, a case is described which is classified using the four‐dimensional epilepsy classification with different degrees of precision by an emergency department physician, a neurologist, and an epileptologist. [ Published with video sequences on www.epilepticdisorders.com ]